Penerapan Strategi Index Card Match dalam Meningkatkan Prestasi Belajar Pada Mata Pelajaran IPA Siswa Kelas IV SD Negeri Inpres Daeo - Subhan Hayun; M. Rais Salim (Peneliti.net, 2020)
The purpose of this research is to determine the application of the Index Card Match strategy in improving learning outcomes in science subjects at the subject of human skeletons and how to care for fourth grade students of SD Inpres Daeo. The type of research used in this research is the Classroom Action Research method which we know as PTK (Classroom Action Research). This research consists of two cycles and in general, there are four stages, namely (1) planning, (2) acting, (3) observing, and (4) reflecting. Based on data analysis and discussion, the conclusions that can be drawn from this study are that the student learning outcomes of the learning material have increased, this can be seen when tests are carried out in the first cycle of students who complete 8 or 40% and in the second cycle when carried out the test increased to 18 or 90%.